769-P: Effect of Food on the Pharmacokinetics, Safety, and Tolerability of Orforglipron (LY3502970), an Oral, Nonpeptide GLP-1 Receptor Agonist - MA, XIAOSU; LIU, RONG; PRATT, EDWARD J.; BENSON, CHARLES; BHATTACHAR, SHOBHA N. (Diabetes (New York, N.Y.), 2023)
Orforglipron [OFG (LY3502970)] is an oral, non-peptide glucagon-like peptide-1 receptor agonist (GLP-1 RA). This reports the results of 2 studies that assessed PK, safety, and tolerability of OFG in healthy subjects, fasted and fed state, after single and repeated doses. Studies A and B were phase 1, randomized, open-label, crossover studies evaluating the effect of food on OFG concentration in healthy adults after a single 3 mg dose (study A) and after a 16 mg daily dose (study B), which was reached by weekly dose escalation starting with 2 mg. Based on statistical analysis, Cmax was 23% (study A) and 21% (study B) lower in the fed state. AUC(0-∞), and AUC(0-24) were 24% (study A) and 18% (study B) lower when administered with food. Tmax and T1/2 were similar with or without food. In study A and B, treatment emergent adverse events (TEAEs) were mild. In study B, TEAEs occurred most often with the starting dose and decreased with dose escalation. The most common TEAEs in study B were decreased appetite (69.7%), nausea (48.5%), and vomiting (45.5%). Overall mean exposure to OFG based on Cmax and AUC was numerically lower when administered with food and had little effect on Tmax and T1/2. Based on exposure response relationship, PK differences are unlikely to result in clinically meaningful differences in OFG safety and efficacy. Phase 3 studies are planned without food or water restrictions.